Aetiology and outcome of neonatal cholestasis in Malaysia - Lee, Way Seah; Chai, P.F.; Boey, Christopher Chiong Meng; Looi, Lai Meng (Singapore Medical Association, 2010)
Introduction: Little is known about the epidemiology, causes and outcomes of neonatal cholestasis in the Asian population beyond Japan and Taiwan. Methods: This was a prospective, observational study on patients with neonatal cholestasis who were referred to the University of Malaya Medical Centre, Malaysia, between November 1996 and May 2004. Results: Biliary atresia (BA) (29 percent) and idiopathic neonatal hepatitis (38 percent) were the two commonest causes of neonatal cholestasis (n is 146) that were referred. Out of the 39 patients (27 percent of the total) who died at the time of review, 35 succumbed to end-stage liver disease. Three of the four patients (three BA, one progressive familial intrahepatic cholestasis PFIC) who had a living-related liver transplant (LT) died after the surgery (two BA, one PFIC). Six (four percent) of the remaining 107 survivors had liver cirrhosis. The overall four-year survival rates for patients with native liver and LT as well as those with native liver alone for all cases of neonatal cholestasis were 72 percent and 73 percent, respectively, while the respective survival rates for BA were 38 percent and 36 percent. Conclusion: BA and idiopathic neonatal hepatitis are important causes of neonatal cholestasis in Malaysian infants. In Malaysia, the survival rate of patients with neonatal cholestasis, especially BA, is adversely affected by the lack of a timely LT.